Economic Value Added (EVA) dan Market Value Added (MVA) pada Perusahaan Telekomunikasi yang Listing di Bursa Efek Indonesia - Fadilah, Kuni; ati, Sumi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This research is puspose to understand about finance performance of telecomunication company whom listed in BEI (Bursa Efek Indonesia). To survey that finance performance we used EVA (economic value added) and MVA (market value added). EVA is the meansures of economic value added which made by corporate as impact of the firm activity and strategy, MVA meansures how much market value added from companies that can be given for investor. EVA is calculated from the result of reduction between Net Operating Profit After Tax (NOPAT) and Cost of Capital. This research used a descriptive kuantitative method. The period of study are 2009-2011 year. The result of this research show that three from five companies of telecomunication corporate is whom listed in BEI 2009-2011 had positive EVA. And all of them had positive MVA. This was showed that all telecomunication companies able to create resource value added for the investor. EVA > 0 is indicate that the companie has good perfomance finance and afford to create economic value added for investor. MVA > 0 is indicate that corporate able to create market value added for the investor. Keywords : Economic Value Added (EVA), Market Value Added (MVA), Net Operating Profit After Tax(NOPAT)